2019
DOI: 10.3390/en12214222
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Latent Carbon Emission Prices for Japan: Theory and Practice

Abstract: Climate change and global warming are significantly affected by carbon emissions that arise from the burning of fossil fuels, specifically coal, oil, and gas. Accurate prices are essential for the purposes of measuring, capturing, storing, and trading in carbon emissions at regional, national, and international levels, especially as carbon emissions can be taxed appropriately when the price is known and widely accepted. This paper uses a novel Capital (K), Labor (L), Energy (E) and Materials (M) (or KLEM) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Energy (E), Intermediate output/input (M) and Services (S). On-going work is using this function to determine carbon output from economic activity and create a forecast value for carbon emission pricing (Chang & McAleer, 2019;Lecca, et al, 2011). Lecca et al propose the function shown in Equation ( 3)…”
Section: Renewable Energy Outputmentioning
confidence: 99%
“…Energy (E), Intermediate output/input (M) and Services (S). On-going work is using this function to determine carbon output from economic activity and create a forecast value for carbon emission pricing (Chang & McAleer, 2019;Lecca, et al, 2011). Lecca et al propose the function shown in Equation ( 3)…”
Section: Renewable Energy Outputmentioning
confidence: 99%
“…Without active measures, it will lead to increasingly serious climate and environmental problems. To better cope with the global warming caused by the greenhouse effect, the United Nations convened a series of climate change conferences and formed a binding greenhouse gas emission agreement (Zhang and Hanaoka, 2021;Chang and McAleer, 2019;Ito, 2019;Wu and Liu, 2020). The main body responsible for reducing emissions in global climate governance began to change from developed countries todeveloped and developing countries, and the constraint form also began to change from compulsory governance to independent responsibility (Wang et al, 2019;Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One key finding of this research is that the cost of shifting to bioplastics in favor of virgin materials is currently the most expensive carbon-reduction option for Japan, compared to the FIT, ETS, energy-system-intervention options, and next-generation vehicles, even for the most cost-effective option (bio-HDPE). In order to close this gap, as has been identified in precedential research, an increase in carbon prices is necessary, as largely envisaged both in Japan and globally [99,100].…”
mentioning
confidence: 99%